CFD model and simulation of pure substance condensation on horizontal tubes using the volume of fluid method. (August 2019) - Kleiner, Thomas; Rehfeldt, Sebastian; Klein, Harald
Graphical abstract: Highlights: Developed CFD condensation model without heuristic or empirical parameters. OpenFOAM solver for overall heat transfer simulation with phase change. Solver has a very good stability even for large temperature gradients. Stefan problem simulations agree with analytic solution. Tube condensation simulations agree with measurements. Abstract: Surface structured tubes show a significant increase in efficiency of condensers, which can decrease the power consumption and CO 2 emission of chemical plants. However, no generalized condensation model for surface structured tubes is developed so far, due to their complex structure. In future works, we aim to use computational fluid dynamics for the investigation of surface structured tubes. Therefore, in this study, we introduce a pure substance condensation model without heuristic or empirical parameters, by means of a new iteration scheme. We show the validation of the newly developed model using the Stefan problem and different simulation approaches for pure substance condensation on a horizontal smooth tube, which are compared to Nusselt's film theory and measurements. The developed model shows a very good simulation stability, even for high temperature gradients. The simulation results of the Stefan problem stand in excellent agreement with the analytic solution. The horizontal smooth tube simulation results give slightly lower heat transfer coefficients compared to Nusselt's film theory, but are in very good agreement to experimental data.